Correlation between nitric oxide and early brain injury after subarachnoid hemorrhage. (3rd July 2015) - Zhao, Dong; Liu, Qi; Ji, Yunxiang; Wang, Ganggang; He, Xuejun; Tian, Weidong; Xu, Hui; Lei, Ting; Wang, Yezhong
Abstract : Background: Early brain injury (EBI) has recently been identified as the main factor of poor prognosis for subarachnoid hemorrhage (SAH), and apoptosis has an important function in EBI. Although nitric oxide (NO) and caspase-12, a specific molecule related to endoplasmic reticulum (ER) stress-induced apoptosis signaling pathways, are involved in brain injury after SAH, the relationship between NO and ER stress has not been reported yet. We examined the NO and caspase-12 contents and investigated the relationship between NO and ER stress-induced apoptosis. Methods: Sprague-Dawley rats ( n = 90), weighing 300 g to 350 g, were used for the SAH model. SAH was induced in rats by blood injection into the prechiasmatic cistern. NO, caspase-12, and apoptosis were measured by nitrate reductase method, real-time polymerase chain reaction, and terminal deoxynucleotidy1 transferase-mediated dUTP nick-end labeling staining, respectively, at different time points after SAH. Pearson correlation coefficients were used to examine correlation. Results: NO level of cerebrospinal fluid significantly increased in the SAH group at 3, 24, 48, and 72 h compared with other groups. Caspase-12 also significantly increased at 1, 3, 6, 24, 48, and 72 h. Cell apoptosis significantly increased at 24, 48, and 72 h. A significant correlation between the number of apoptotic neurons and caspase-12 was found. NO was also correlated with caspase-12. Conclusions: Our results suggest that NO is involved in the pathophysiological events of EBI after SAH by increasing caspase-12, which results in neuronal apoptosis.